Applying Structural Equational Model (SEM) to Analysis of Perceived Social Media Influence on Intention to Buy Online Store by Consumer Trust and Hedonic Brand Image - Wisnalmawati, Wisnalmawati; Annegrat, Ahmed Mohamed; Rahadini, Marjam Desma; Sanosra, Abadi; Suryono, Agus (Universitas Negeri Semarang, 2024)
Purpose: This research aims to examine the influence of social media perceptions which directly influence repurchase intentions which are mediated by consumer trust and hedonic brand image in an online shop by applying the Structural Equational Model (SEM) with Partial Lease Square (Smart PLS) technique.Methods: This research examines the effect of social media perception intervention on repurchase intentions which is analyzed with a population taken from consumers in four marketplaces, including Lazora.Com, Lazada.com, and Blibli.com. bukalapak.com. The number of samples in this research was 80 respondents. The sampling technique uses accidental, namely distributing questionnaires to consumers who meet in WhatsApp groups. The data was tested with the variable social media perception, purchase intention, consumer trust, and hedonic brand image. Data were analyzed using the Structural Equational Model (SEM) with Partial Lease Square (Smart PLS) technique.Result: The research results show that the indicator variables proposed to test the influence of perceived social media on repurchase decisions. The Q2 predictive relevance value shows that the perceived social and consumer trust contributes 0.7647 towards the intention to buy. The rest which is 0.2353 is affected by the other variable. Therefore, social media perceptions do not influence repurchase intentions, but social media perceptions influence repurchase intentions which are mediated by consumer trust and Hedonic Brand Image in an online shop.Research limitation: We found that there are perceived social media influence repurchase intention to buy mediated by consumer trust and Hedonic Brand Image in an online store. This will contribute to other research, creating Consumer trust and a Hedonic Brand image is very important to increase repurchase intention to buy in an online store. Practical implications – The findings of this study may contribute to consumer behavior models, online stores, and Tripple duties.Novelty: The novelty of this research is that consumer trust and hedonic brand Image can increase the intention to buy in an online store.